2021
DOI: 10.22460/project.v4i1.p80-85
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Deixis in “Nom Nom’s Entourage” Manuscript on We Are Bare Bears Movie Season

Abstract: The tittle of this research is An AnalysisDeixis in “Nom nom’s Entourage” Manuscript on We are Bare BearsMovie Seaso. Deixis is one of branch from pragmatics that shown relation between language and context in that language it self. The aim from this research is to know and identify the type of deixis in Nom nom’s Entourage movie season. That have some steps to collecting the data firs is watching the We Are Bare Bears movie season with Nom nom’s Entourage title. Second is reading the script of that movie. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Traditional research on deixis has not been able to confine its observations to deictic markers but has tended to flow over into the realm of imaginative reconstruction of speech modality. There have been many studies conducted related to deixis [7]- [11]. However, this present study is considerably different from earlier research, as it analyzes the actual types of deixis found in the Raya and The Last Dragon scripts.…”
Section: Introductionmentioning
confidence: 83%
“…Traditional research on deixis has not been able to confine its observations to deictic markers but has tended to flow over into the realm of imaginative reconstruction of speech modality. There have been many studies conducted related to deixis [7]- [11]. However, this present study is considerably different from earlier research, as it analyzes the actual types of deixis found in the Raya and The Last Dragon scripts.…”
Section: Introductionmentioning
confidence: 83%